2016
DOI: 10.1155/2016/5424713
|View full text |Cite
|
Sign up to set email alerts
|

Refractive and Quality of Vision Outcomes with Toric IOL Implantation in Low Astigmatism

Abstract: Purpose. To evaluate the refractive and the quality of vision outcomes of toric IOL implantation in patients with low astigmatism. Design. Prospective study of single-arm. Methods. Patients with corneal astigmatism range from 0,75 D to 1,5 D and cataract that underwent cataract surgery with toric IOL. The measurements were performed preoperatively and 6 weeks after the surgery. Patients were evaluated for visual acuity with and without correction, contrast sensitivity, static and dynamic refraction, and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
(27 reference statements)
2
11
0
1
Order By: Relevance
“…The majority of patients achieved highly significant UDVA and CDVA improvement. The current results are consistent with those previously reported for a number of toric IOLs, including Bi-Flex T, AcrySof, Rayner T-Flex ® and TECNIS ( 1 , 4 , 9 , 18 ). There was no difference between the two groups in postoperative residual astigmatism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The majority of patients achieved highly significant UDVA and CDVA improvement. The current results are consistent with those previously reported for a number of toric IOLs, including Bi-Flex T, AcrySof, Rayner T-Flex ® and TECNIS ( 1 , 4 , 9 , 18 ). There was no difference between the two groups in postoperative residual astigmatism.…”
Section: Discussionsupporting
confidence: 93%
“…With the improved quality of life, cataract surgery has developed from a procedure for removing the cloudy lens safely so patients can acquire freedom from glasses and gain excellent uncorrected visual acuity ( 7 , 8 ). When patients undergo cataract surgery, implantation of toric IOL is deemed the most effective choice for correcting corneal astigmatism and reducing postoperative spectacle dependence ( 9 ). Nonetheless, fluctuating or inaccurate preoperative keratometry ( 10 ), undervaluation of the total astigmatism in IOL power calculations ( 11-13 ), unexpected surgically induced astigmatism ( 14 ), errors of IOL axis position ( 15 ), or IOL instability ( 16 ) could decrease the curative effect of toric IOL.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that eyes with a preoperative corneal astigmatism between 0.75D and 1.5D could benefit from a toric IOL. 9 A large number of risk factors was identified in our study. Poor preoperative visual acuity is one such risk factor probably because the patient's inability to fixate properly during biometry measurement.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, implantation of a toric IOL is strongly recommended for patients with both cataract and corneal astigmatism [19] [20]. However, myopic patients who determined to nearsighted target such as -3D have to wear spectacle as usual after surgery, so the remaining astigmatism can be corrected by spectacle.…”
Section: Discussionmentioning
confidence: 99%